Bridging the Pacific Ocean? Tactical Maneuvering Instead of Grand Strategy in Chile's Foreign Policy toward Southeast Asia. Issue 2 (17th May 2020) - Jenne, Nicole
Abstract : Chile often portrays itself as Latin America's bridge to Asia, where the ASEAN countries have been singled out as its new priority. Yet, it is not difficult to see that Chile, a small and peripheral state, does not actually serve as a gateway between Latin America and Southeast Asia. This article argues that Chile has lacked consistency in its approach toward Southeast Asia as well as focus of purpose to become a bridge‐builder due to the structural constraints faced by a small state. Based on an analytical framework of small states' foreign policies, I revisit Chile's relations with Southeast Asia, pointing to factors driving and limiting deeper engagement with the distant region. The analysis shows that a risk‐adverse, low‐profile approach of tactical maneuvering has served Chile's objectives even though it is insufficient to bridge the Pacific Ocean. The article concludes with a reflection on this trans‐Pacific relationship. Abstract : 跨越太平洋？智利对东南亚外交政策中用策略操纵替代大战略: 智利经常将自身描述为通往亚洲的拉美桥梁，东盟国家已经将其选择为新的政策重点对象。然而不难看出，智利这一发挥边缘作用的小国并不能真正充当拉美与东南亚之间的桥梁。本文主张，鉴于一个小国所面临的结构限制，智利无法始终践行其对东南亚的外交政策，也无法始终聚焦于成为桥梁搭建者这一目的。基于一项有关小国外交政策的分析框架，我重新审视了智利与东南亚的外交关系，指出了与远距离地区进行更深入接触的驱动和限制因素。分析表明，采用风险厌恶、低调的策略方法一直是智利的目标，尽管其不足以跨越太平洋。本文结论反思了跨太平洋关系。 Abstract : ¿Construyendo puentes sobre el Océano Pacífico? Maniobras tácticas en lugar de una gran estrategia en la política exterior de Chile hacia el Sudeste Asiático: Chile a menudo se presenta como el puente de América Latina hacia Asia, donde los países de la ASEAN se han convertido en su nueva prioridad. Sin embargo, no es difícil ver que Chile, un pequeño estado periférico, en realidad no sirve como puerta de enlace entre América Latina y el Sudeste Asiático. Este artículo argumenta que Chile ha carecido de consistencia en su enfoque hacia el Sudeste Asiático, así como en su objetivo de convertirse en un constructor de puentes debido a las limitaciones estructurales que enfrenta un estado pequeño. Basado en un marco analítico de las políticas exteriores de estados pequeños, reviso las relaciones de Chile con el Sudeste Asiático, señalando los factores que impulsan y que limitan un compromiso más profundo con la región distante. El análisis muestra que un enfoque de maniobras tácticas de bajo perfil y adverso al riesgo ha servido a los objetivos de Chile a pesar de que es insuficiente para tender un puente sobre el Océano Pacífico. El artículo concluye con una reflexión sobre la relación transpacífica.